Proceso de ASC - VIOLONCHELO EN COLOMBIA. LISTADO DE OBRAS ESCRITAS ENTRE 1964 y 2022 POR MUJERES COMPOSITORAS. PREPARACION PARA LA EDICION DE LAS OBRAS DE JAQUELINE NOVA SONDAG (2022)
The doctoral thesis of Javier Arias from the National Autonomous University of Mexico collects 139 works located for cello, solo, duo, for multiple cellos and as a solo instrument written by composers in Colombia during 1896 to 2017 for a total of 67 creators of which 57 are men and only 10 women. The present research project seeks to answer a) why is there such a discrepancy in the range of men composers vs, women composers, b) why women composers and their works are not being considered in the same manner that those from male composers, c) how professional training for cellists in Colombia has commonly been addressed in the different educational institutions and how they formulate their curricula, d) why the study of works by Colombian composers has not been contemplated, e) what happened to the music for cello written by women composers since 2017 up to 2022. Javier Arias points out in his doctoral thesis that since there has not been a systematization and classification of works for cello written in Colombia, it is very difficult to promote the use of these works. Some professors from institutions of higher education had previously addressed the issue, and joined efforts so that, at least in their chairs, some of the repertoire could be used. However, it cannot be said that such efforts have been coordinated and generalized for all institutions: rather, they were specific cases. These problems generated the idea of the formulation of a research project that would contribute to making works from male and female composers equally known and accessible through the dissemination of their works and their implementation in the cello curricula. This research project was officially consolidated in 2022 to locate, classify and systematize the works for cello written by women composers in formats such as solo cello, duet, multiple cellos as well as soloist instrument written between 2017 and 2022 to promote and make them accessible to the actors of interest. It is important to clarify the figure of Jacqueline Nova Sondag, a pioneer and promoter of electroacoustic music in the country who was the first woman to graduate with a title in composition and an important reference of composition in Colombia. Her works with cello are: "Scherzo in primitive style" for violin and cello, composed in 1964, “Mesure” for cello and piano written in 1965, and "Scherzo bitonal" for viola and cello, from 1967. These works were the first ones found written by a woman composer, therefore are of high importance for publishing. In addition to preparing Sondag's works, this project seeks to compile and classify the works of Colombian women composers from 2017 to 2022 who, with their works, have contributed significantly to enriching the repertoire in question. With the data provided by composer Melisa Vargas Franco, it has been possible to search via email and social networks for the composers mentioned there. In addition to this, a call was made on Instagram, as a search, to which some composers who provided their works responded. With the above, 29 works were compiled in the various formats already mentioned and a consolidated of 18 composers among which are Violeta Cruz (Bogotá, 1986), Carolina Noguera Palau (Cali, 1979), Alba Fernanda Triana (Bogotá, 1969), Susana Vásquez (Medellín, unknown) Laura Fernanda Zúñiga (Bogotá, unknown), Laura Zapata Cortés (no data), Erika Sáenz Burdón (no data), Manuela Pulido Gutiérrez (no data), Maria Eugenia Gómez (no data) and Leidy Montilla (no data), all of them with one work; Claudia Calderón (Palmira, 1959), Alba Lucía Potes (Cali, 1954), Natalia Valencia (Medellín, 1976), Ana María Franco (no data), Michele Abondano (no data) and Laura Echeverri Rendón (no data) with two works each and Paola Arévalo Lasso (no data), with four works.